Comparative folate metabolism in humans and malaria parasites (part I): pointers for malaria treatment from cancer chemotherapy. - Nzila, A; Ward, SA; Marsh, K; Sims, P; Hyde, J (2005)
New inhibitors are urgently needed to overcome the burgeoning problem of drug resistance in the treatment of Plasmodium falciparum infection. Targeting the folate pathway has proved to be a powerful strategy for drug development against rapidly multiplying systems such as cancer cells and microorganisms. Antifolates have long been used for malaria treatment but, despite their success, much less is known about parasite folate metabolism than about that of the human host. In this article, we focus on folate enzymes used clinically as anticancer drug targets, in addition to those that have potential to be used as drug targets, for which there are inhibitors at various stages of development. We discuss how this information could lead to the identification of new targets in malaria parasites.